Synthesis and characterizations of ethylbutyldithiocarbamate compounds: crystal structure of bismuth(III) ethylbutyldithiocarbamate - Karimah Kassim,; Ibrahim Baba,; Yang Farina ,; Abdul Hamid Othman,; H.K. Fun, (Universiti Kebangsaan Malaysia, 2002)
A new series of ethylbutyldithiocarbamate compounds have been synthesized. The compounds made of Zn(II), Cu(II), Ni(II), Pb(II), Sb(III) and Bi(III) were prepared by reacting the respective metal salts with ethylbutylamine and carbon disulphide using "in situ" method. Results of elemental analysis showed that the isolated compounds have the general formula, M[S2CNR1RZ2]n (n = 2; M = Zn(II), Cu(II), Ni(II), Pb(II), and n = 3; M = Sb(III) and Bi(III)). Infrared spectra of the compounds showed the thioureido v(C-N) bands in the regions 1468 – 1497 cm-1. The (C-S) bands appeared in the region 956 – 997 cm-1 while the v(M-S) bands appeared in the region 300 – 400 cm-1. The 1H NMR signals indicated ethyl- and butyl- in the region 0.40 – 3.85 ppm. The 13C NMR spectra of zinc(II) and lead(II) showed a resonance in the region 202.0 ppm, which attributed to the carbon atom of NCS2 group. Tris(N-ethyl-N-butyldithiocarbamato-S) bismuth(III) is pentagonal pyramid distorted with triclinic system with P1, a = 10.5120(1)Å, b = 10.5128(1)Å, b = 10.5128(1)Å, c = 14.5755(1)Å, α = 99.927(1)o, γ = 103.3383(1) and Z = 2.